2007
DOI: 10.1038/nn2006
|View full text |Cite
|
Sign up to set email alerts
|

RGS2 modulates coupling between GABAB receptors and GIRK channels in dopamine neurons of the ventral tegmental area

Abstract: Agonists of GABA(B) receptors exert a bi-directional effect on the activity of dopamine (DA) neurons of the ventral tegmental area, which can be explained by the fact that coupling between GABA(B) receptors and G protein-gated inwardly rectifying potassium (GIRK) channels is significantly weaker in DA neurons than in GABA neurons. Thus, low concentrations of agonists preferentially inhibit GABA neurons and thereby disinhibit DA neurons. This disinhibition might confer reinforcing properties on addictive GABA(B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
240
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 185 publications
(255 citation statements)
references
References 49 publications
14
240
1
Order By: Relevance
“…The enhanced RGS2 membrane translocation may underlie subsensitivity of D2 autoreceptor following AMPH self-administration. It has been demonstrated previously that RGS2 mRNA is expressed in dopaminergic neurons as shown by quantitative gene expression analysis in single cells (Labouebe et al, 2007). We further confirmed that RGS2 protein exists in the midbrain dopaminergic neurons by immunocytochemistry.…”
Section: Amph Self-administration Selectively Promoted Membrane Transsupporting
confidence: 84%
“…The enhanced RGS2 membrane translocation may underlie subsensitivity of D2 autoreceptor following AMPH self-administration. It has been demonstrated previously that RGS2 mRNA is expressed in dopaminergic neurons as shown by quantitative gene expression analysis in single cells (Labouebe et al, 2007). We further confirmed that RGS2 protein exists in the midbrain dopaminergic neurons by immunocytochemistry.…”
Section: Amph Self-administration Selectively Promoted Membrane Transsupporting
confidence: 84%
“…The VTA DA neuron GIRK channel (GIRK2/GIRK3) is unique, as most neuronal GIRK channels contain GIRK1 (Cruz et al, 2004;Koyrakh et al, 2005;Labouebe et al, 2007). Interestingly, Girk2 ablation yields a complete loss of VTA DA neuron GIRK channel activity (Beckstead et al, 2004;Cruz et al, 2004), whereas Girk3 ablation yields increased sensitivity of the residual channel (GIRK2 homomer) to receptor activation (Labouebe et al, 2007;Lunn et al, 2007).…”
Section: Girk-dependent Inhibitory Feedback and Cocaine Reinforcementmentioning
confidence: 99%
“…Interestingly, Girk2 ablation yields a complete loss of VTA DA neuron GIRK channel activity (Beckstead et al, 2004;Cruz et al, 2004), whereas Girk3 ablation yields increased sensitivity of the residual channel (GIRK2 homomer) to receptor activation (Labouebe et al, 2007;Lunn et al, 2007). The opposing contributions of GIRK2 and GIRK3 are also sensed at the behavioral level, where loss of GIRK2 in DA neurons correlates with increased locomotor effects of cocaine and morphine, while constitutive Girk3 ablation correlates with decreased locomotor-stimulatory effect of morphine (Arora et al, 2010;Kotecki et al, 2015).…”
Section: Girk-dependent Inhibitory Feedback and Cocaine Reinforcementmentioning
confidence: 99%
“…Previous studies have shown that D 2 autoreceptormediated inhibition of VTA dopamine neurons is reduced after repeated psychostimulant exposure (Henry et al, 1989;Marinelli et al, 2003;Wolf et al, 1993), whereas the GABA B receptor-GIRK channel coupling efficiency is increased after repeated exposure to morphine or the GABA B agonist g-hydroxybutyrate (Labouebe et al, 2007). In this study, by performing patch-clamp recordings from putative dopamine neurons in the VTA of mouse brain slices, we show that repeated in vivo exposure to ethanol induces sensitization of D 2 -mediated inhibition without affecting GABA Bmediated inhibition.…”
Section: Introductionmentioning
confidence: 98%
“…It is well known that activation of dopamine D 2 receptors and GABA B receptors can mediate powerful inhibition of dopamine neurons both in vitro (Beckstead et al, 2004;Labouebe et al, 2007;Lacey et al, 1987) and in vivo (Erhardt et al, 2002;White and Wang, 1984). These receptors are coupled to the activation of G protein-gated inwardly rectifying K + (GIRK) channels via G i/o G proteins, resulting in membrane hyperpolarization and suppression of neuronal excitability (Luscher and Slesinger, 2010).…”
Section: Introductionmentioning
confidence: 99%